Grid to Vehicle and Vehicle to Grid (V2G) Overview in the Smart Grid - Fathurrahman Fathurrahman (CIRCUIT: Jurnal Ilmiah Pendidikan Teknik Elektro, 2017)
The grid to vehicle context in this report referred to the current status of the vehicle charging system that supported by the grid and its implication to the grid. The electric vehicle also can be exploited and treated as the mobile energy storage that has the capability to inject the power back to the grid. The idea of transfer back power the grid from electric vehicle is commonly known as V2G. In total, the cumulative horse power that millions vehicle have are tens times larger than the total of all electricity generating capacity in the world. However, due to the technical issue, the vehicle potential could not be tap to contribute to the grid until the birth of current concept of so called V2G. V2G is relatively a new technological breakthrough, which not only support the grid but also could potentially accelerate the process of creating a smarter grid.